Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/21655979.2017.1304872
|View full text |Cite|
|
Sign up to set email alerts
|

A strategy for L-isoleucine dioxygenase screening and 4-hydroxyisoleucine production by resting cells

Abstract: L-Isoleucine dioxygenase (IDO) specifically converts L-isoleucine(L-Ile) to 4-hydroxyisoleucine(4-HIL). To obtain IDO with improved activity, a strategy was developed that is dependent on the restoration of succinate-minus E. coli cell growth by the coupling of L-Ile hydroxylation and the oxidation of α-ketoglutarate(α-KGA) to succinate. Five mutants were obtained with this strategy, and the characteristics of IDOM3, which exhibited the highest activity, were studied. The catalytic efficiency, thermal stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Using this strain, 4-HIL yields were found to be 82%, employing 100 mmol L-isoleucine as a substrate [50]. Recently, Zhang et al enhanced the activity of IDO by introducing four mutations, which were identified by error-prone PCR [66]. Using this approach, the The enzymes typically accept free-standing amino acids as a substrate.…”
Section: L-isoleucine 4-hydroxylase or L-isoleucine Dihydroxygenase (Ido)mentioning
confidence: 99%
See 2 more Smart Citations
“…Using this strain, 4-HIL yields were found to be 82%, employing 100 mmol L-isoleucine as a substrate [50]. Recently, Zhang et al enhanced the activity of IDO by introducing four mutations, which were identified by error-prone PCR [66]. Using this approach, the The enzymes typically accept free-standing amino acids as a substrate.…”
Section: L-isoleucine 4-hydroxylase or L-isoleucine Dihydroxygenase (Ido)mentioning
confidence: 99%
“…Using this strain, 4-HIL yields were found to be 82%, employing 100 mmol L-isoleucine as a substrate [50]. Recently, Zhang et al enhanced the activity of IDO by introducing four mutations, which were identified by error-prone PCR [66]. Using this approach, the k cat /K m value of IDO could be increased 1.5-fold to reach approximately 33 L/mmol/min, and the 4-HIL production doubled in a small-scale biocatalysis reaction [66].…”
Section: L-isoleucine 4-hydroxylase or L-isoleucine Dihydroxygenase (Ido)mentioning
confidence: 99%
See 1 more Smart Citation
“…4-HI is an amorphous, hydrophilic powder with a molecular weight of 147.17 grams per mole (Broca et al, 2004). It is produced from an amino acid, isoleucine, by the activity of bacterial isoleucine dioxygenase and has a high therapeutic potential in treating insulin dysregulation (Zhang et al, 2018). 4-HI has been reported to demonstrate peculiar therapeutic bene ts against insulin resistance, inadequate glucose absorption, lipotoxicity, obesity, and liver dysfunctions (Soriano et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the -KG concentration has a significant effect on l-Pro hydroxylation. Zhang et al overexpressed -KG dehydrogenase (ODHC) gene and knocked out isocitrate lyase gene aceA in E. coli, where exogenous IDO shunted the flux of -KG to the pathway of 4-HIL production (10). The other approach to redirecting the flux of -KG to 4-HIL was ODHC inhibition.…”
Section: Introductionmentioning
confidence: 99%